NEW EMPHASES ON THE STUDY OF THE PATHOGENESIS OF CHRONIC HEART FAILURE WITH PRESERVED EJECTION FRACTION: FOCUS ON INFLAMMATORY MARKERS - O. M. Drapkina; L. O. Palatkina (Столичная издательская компания, 2015)
For the long time the systolic myocardial dysfunction was traditionally associated with the severity of chronic heart failure (CHF). Increasing number of patients with symptoms of CHF but without systolic dysfunction has drawn the attention of specialists to so-called CHF with preserved ejection fraction. Prognosis in CHF with preserved ejection fraction may be as bad as in CHF with reduced ejection fraction. Significant changes in views on the pathogenesis of CHF led to the creation of new therapeutic approaches in the treatment of this disease. However, at present, convincing evidence base of mortality reduction in patients with CHF with preserved ejection fraction using well-known therapeutic agents is unavailable. It makes conduct active searches for new biological markers of diastolic heart function. Participation of proinflammatory cytokines, in particular GDF-15, in the process of elasticity reduction and relaxation disorders of left ventricular myocardium, may be of great importance in the development of new medical agents designed to delay the progression of CHF with preserved ejection fraction.